Mood State of Women with Breast Cancer and that of Their Spouses - Luz Stella Bueno Robles; Virginia Inés Soto Lesmes (Universidad de Antioquia, 2016)
Objectives. This work sought to determine mood levels of women subjected to treatments for breast cancer and of their spouses. Methods. Descriptive cross-sectional study with non-probabilistic sampling. The profile of mood states (POMS) instrument, Spanish version, was applied to a sample of 103 couples from five Colombian cities. Results. The mood level in women reported a mean of 61.4 ± 5.7 and 60.7 ± 4.9 in their spouses, without being statistically significant. Upon analyzing the score of the mood subscales, statistically significant differences were only noted in tension (higher score in spouses) and fatigue (higher score in women). Conclusion. The emotional area was moderately affected in the study couples, which could be consequential of late effects of the treatments for breast cancer. Nursing must develop care actions that promote the emotional wellbeing of women with breast cancer and include participation from the spouses.   How to cite this article: Bueno-Robles LE, Soto-Lesmes VI. Mood State of Women with Breast Cancer and that of Their Spouses. Invest. Educ. Enferm. 2016; 34(3): 537-543.